NILAI PERUSAHAAN PADA INDUSTRI MOBIL DI BURSA EFEK CHINA: DITINJAU DARI CURRENT RATIO, PERTUMBUHAN, UKURAN PERUSAHAAN DAN ROE SEBAGAI VARIABEL INTERVENING - Pang Hao; Hery Krisnandi (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the effect of Liquidity, Company Growth and Company Size on Firm Value with Profitability as an intervening variable in the Car Industry on the China Stock Exchange in 2017-2021. This research is quantitative descriptive. Data analysis used a path test with structural equation modeling (SEM) with the partial least squares (PLS) method and 2023 SmartPLS Program. The results showed that: (1) Current ratio has no direct significant effect on firm value, (2) Company growth has a direct significant effect on firm value, (3) Company size has no direct significant effect on firm value, (4) ROE has a direct significant effect on firm value (5) Current ratio has a direct significant effect on ROE, (6) Company growth has no direct significant effect on ROE, (7) Company size has a direct significant effect on ROE, (8) ROE does not mediate significant effect between the current ratio and firm value, (9) Company ROE does not mediate a significant effect between firm growth and firm value, (10) ROE does not mediate a significant effect between firm size and firm value.